Pemberdayaan Ibu dan Keluarga Melalui Edukasi Asuhan Komplementer Pijat Laktasi Pada Ibu Nifas dan Menyusui untuk Mendukung Keberhasilan Menyusui di Puskesmas Saigon - Asmaurina Pramulya; Anastasia Lina; Agnes Dwiana Widi Astuti; Efrosina Ludovika Kalista; Odilya Firmatary; Anjelina Sera (PELANTAR PRESS, 2026)
Lactation massage as a complementary care that can increase breast milk volume and provide a relaxing effect on postpartum mothers. The implementation of lactation massage in first-level health facilities such as Community Health Centers has the potential to reduce the incidence of breast engorgement or breast milk stagnation. The activity was carried out by explaining the objectives of Community Service on lactation massage material using leaflets and educational videos, as well as practicing how to perform lactation massage using educational dolls and performing massage directly on postpartum and breastfeeding mothers (Demonstration and Rededication). The results of this Community Service were that all 30 participants received education that had been provided in the form of leaflets, educational videos, demonstrations using educational dolls and then redemonstrated to all participants, after which the Community Service team performed lactation massage to participants one by one until all participants. All outputs (leaflets, videos, and educational dolls) interact with each other in one educational system. The progress that has been achieved has met the target of implementing activities that have been carried out at the Saigon Community Health Center. Structured education supported by appropriate demonstration media can change the public paradigm regarding lactation barriers for breastfeeding mothers to recognize their body's needs independently.